Femtosecond optical-to-microwave frequency divider with a relative instability of. (December 2016) - Kireev, A.N.; Tausenev, A.V.; Tyurikov, D.A.; Shelkovnikov, A.S.; Shepelev, D.V.; Konyashchenko, A.V.; Gubin, M.A.
Abstract: We have developed a low-noise optical-to-microwave frequency divider based on a femtosecond erbium fibre laser. The source of an optical signal was a frequency standard. Comparison of two frequency dividers showed that the relative instability of output microwave signals, introduced by the dividers, is for the averaging time . The instability obtained corresponds to the requirements imposed on interrogative oscillators for time and frequency standards based on Cs or Rb atomic fountains.